Basic Income, Eco-logical Ethics, and Interdependent Well-Being - Sisler, Aiden (ETHICS IN PROGRESS, 2014)
A Basic Income (universal basic income or citizen’s income) could contribute to the means for living a dignified ecologically- and socially-aligned life characterized by well-being, freedom, and equality. After laying out key definitions, I reflect on moral and ethical issues regarding Basic Income’s implementation, backed by supportive theory and evidence. These arguments organise around interdependence in eco-social systems and core requirements of ontogenesis as well as the intersection and intertwining of socio-cultural, political, and economic factors, known as socio-ecological determinants of global health and well-being. Following that, I briefly make the case for why intersectional and intersubjective aspects should be closely held in contextualized view of Basic Income’s democratised drafting and provision.